Complex minimax programming - Liu J.C. (Utilitas Mathematica, 1999)
We establish the Kuhn-Tucker type necessary and sufficient optimality conditions for complex minimax programming with generalized convex functions. Subsequently, we apply these optimality criteria to formulate two dual problems. We also establish weak, strong, and strict converse duality theorems.